ANALYSIS OF GENDER DEVELOPMENT AND ITS IMPACT ON ECONOMIC GROWTH IN BALI - Made Astrama, I (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2022)
The Gender Equality Index released by Equal Measures; Indonesia got mixed results on various indicators that were used as references. For example, Indonesia has been praised for recording one of the highest literacy rates in Asia (93.59% for women and 97.17% for men). Demographic changes in Indonesia by referring to the variables of population growth, life expectancy and the growth of the ratio of workers to the total population have a big influence on Indonesia's economic growth. The implication of these variables is economic growth. Besides that, it can also be explained that until now the Indonesian economy is still supported by household consumption, with the proportion of household consumption to GDP. Ease of access to technology will also increase women's productivity.